Sufistic Monotheism: Divinity in the Anthropocentric Reasoning of Ibn 'Arabi's Wahdat al-Wujud - Badar, Miftahul; Riyadi, Abdul Kadir (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
This paper discusses the concept of divinity in the anthropocentrism of Ibn 'Arabi's wahdat al-wujud thought system through library research. Wahdat al-wujud's anthropocentrism reasoning assumes that humans are the most perfect manifestation of God. The human body is a microcosm, whereas the universe is a macrocosm. Humans are God's creations that have the potential to receive the totality of the divine image and reflect it for the entire universe, while God's other creations can receive only a part of it. Thus, man is the totality of the divine image and reality of the universe. Humans have a noble position in the cosmos, which becomes their spirit and purpose, including their relationship with God. In the anthropocentrism of waḥdat al-wujūd, God is not understood as far away, but as near: the human self. God is not another being but the human self. Therefore, man is required to know himself, and he will surely know his God. Without self-knowledge, humans are unable to know God.